STUDY OF WATER RESISTANCE OF COAL BRIQUETTES - Холмуродова Д. К.; Меликулов О. Ж.; Исломов Л. Б. (Galaxy International Interdisciplinary Research Journal, 2023)
In the work, the study of the water resistance of coal briquettes obtained the optimal content of the binder. It has been established that the product has high quality characteristics.